Decision Support System for Determining Employee Appointment Stick with the Method Balanced Scorecard and Analytic Network Process: Sistem Pendukung Keputusan Penetapan Pengangkatan Karyawan Tetap menggunakan Metode Balanced Scorecard dan Analitik Proses Jaringan - Ikhsan Rahdiana; Firdha Aprilyani (Universitas Singaperbangsa Karawang, 2021)
Contract employees are employees whose job status within the company does not have facilities and does not ensure the continuity of their work in the company. Determination of contract employees to become permanent employees at PT Menara Antam Sejahtera is still not fair and requires sufficient time long. In determining contract employees to become permanent employees, it is carried out in stages by file selection, oral or written tests, and direct observation to employees so that mistakes are made in determining the final result of the determination of contract employees can be minimized. For determination, the ppointment of contract employees to become permanent employees is one way touse the approach method Balanced Scorecard. The next stage is processed using the Analytic Network Process. With the help of Super Decision software, a decision support system is made in terms of determining permanent employees at PT Menara Antam Sejahtera with a promotion of 0.33360 in the normalized by cluster table based on promotions, employee performance becomes more objective and make more efficient.